(untitled) (Journal of Dhaka Medical College, 2018)
Background/context: Dietary diversity (DD) is universally recognized as a key component of healthy diets. Healthy diet is one of the most important determinants that can influence nutritional status of women of reproductive age. Materials and Methods: This cross sectional study was conducted in Shitpara village of Sreepur Upazila under Gazipur district during February to June 2013 to assess the dietary diversity and nutritional status of women of reproductive age. Convenient sampling technique was adopted to select 181 women. Interview schedule & checklist used as research instrument. Results: The mean(+/-s.d.)age of the respondents was 27.45+/-9.38 years, 133(80%) of them were married and 176(97.2%) are literate. Mean family size was 5.34+/- 2.386 persons and mean family income was 9611.05 Taka per month. Among 133 married women, 68(51%) have 2 or less than two children. Their mean(+/-s.d.) dietary diversity score was 5.13+/- 1.19 and majority 149(82%) of them having medium dietary diversity tercile (4-6). All of them ate carbohydrate types of food, 174(96.1%) protein rich foods & 83(45.9%) vit.A rich vegetables & fruits. Their mean BMI was 22.35 +/- 3.71 kg/ m2. Majority 118 (65%) of them having normal BMI and 22(12%) are under weight. Only 6(3%) of them are obese. Thoughdietary diversity was medium (4-6); relationship between dietary diversity and nutritional status could not be established. Conclusion:The qualitative measurement of dietary diversity is not sufficient enough to identify women at risk of under- or over nutrition. J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 36-40